PERANCANGAN LUMBAR SUPPORT TERHADAP KELUHAN MUSKULOSKELETAL PADA LINGKUNGAN KERJA PERKANTORAN - Hidayat, Michael; Widodo, Lamto; Sukania, I Wayan (Jurnal Mitra Teknik Industri, 2025)
Office workers are at high risk of developing musculoskeletal disorders due to prolonged static sitting positions. This study was conducted at the Indonesia Exim bank to explore the relationship between office chair design particularly the presence of lumbar support and musculoskeletal complaints. The methods used included questionnaires, as well as assessments using RULA and the Nordic Body Map, involving 32 participants. The results indicated that the lower back and waist were the most frequently reported areas of discomfort. Although the chairs used were ergonomically designed, the lumbar support was not optimal. By designing a lumbar support based on anthropometric data, a significant improvement in posture comfort was observed.